Two alternative synthesis routes for MnZn ferrites using mechanochemical treatments - Botta, Pablo Martín (2006)
Two different methodologies to synthesise MnxZn1-xFe2O4 (x = 0.5, 0.65 and 0.85) are compared. In the first method, mechanochemically activated mixtures of elemental oxides were thermally treated at 1100 and 1200 °C under N2 atmosphere. In the second, previously obtained MnFe2O4 and ZnFe2O4 were well-mixed and treated at 1100 °C under N2 atmosphere. Both series of materials were characterised by X-ray diffraction (XRD), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM), electron probe microanalysis and density measurements. Through a two-step processing, both methods allowed to obtain MnZn ferrites of several compositions, which exhibited high saturation magnetisations and very low coercivities. In this way, in order to overcome some limitations of the conventional preparation technique, alternative synthesis routes for these ferrites are proposed in this study.